The Correlation Between Husband Support And Lifestyle With Nutritional Status Of Implant KB Accepters At Puskesmas Plus Perbaungan, Serdang Bedagai Regency, 2022 - Simanjuntak, Lisdayanti; Bui, Thanh Loan; Sinaga, Rosmani; Gurning, Lisbet; Rajagukguk, Kristina; Berutu, Lilis (Jurnal EduHealth, 2022)
The Family Planning Program (KB) is a government program that seeks to reduce population growth and maternal mortality (Zuhana & Suparni, 2016). The largest type of contraception used in Indonesia is hormonal contraception (Hadisaputra & Sutrisna, 2014). The achievement of active implanted family planning participants in Indonesia in December 2016 amounted to 582,352 (14.6%) (BKKBN, 2017). Implant contraception is one of the long-term contraceptive methods. The prevalence of implant type MKJP users in North Sumatra in 2016 occupied the largest number compared to IUD, MOP and MOW type MKJP users. There are 492,803 active MKJP KB implant users in North Sumatra (9.9% of the total MKJP users in North Sumatra) (BKKBN North Sumatra Province, 2017). In Medan, active KB implant participants in 2016 amounted to 13,636 (3.73% of the total active KB users in Surabaya).